2008
DOI: 10.1007/s12523-009-0008-3
|View full text |Cite
|
Sign up to set email alerts
|

Überprüfung der im Rahmen des „Lebenserwartungssurveys“ gemessenen Sterblichkeit auf Bevölkerungsrepräsentativität unter Berücksichtigung rechts- und intervallzensierter Ereignisse mit dem Konzept „Relative Survival“

Abstract: Zusammenfassung: Der Lebenserwartungssurvey (LES) ist einer der wenigen überregi-onalen Längsschnittdatensätze in Deutschland. Für eine Beobachtungszeit von maximal 14 Jahren (1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998) lässt sich der Survivalstatus der Stichprobenmitglieder verfolgen. Durch die Verknüpfung mit den vielfältig erhobenen personenge bundenen Informationen zu sozioökonomischen, demographischen, gesundheitsrelevanten und medizinischen Merkmalen bietet d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For 1,047 women (25.3 percent) and 903 men (20.8 percent) the survival status by 1998 is unknown. Tests of the quality of the LES mortality data revealed that the refl ected survival of the LES sample between 1984 and 1998 is representative for the western German population, regardless of whether individuals with unknown survival status in 1998 are included or not (Luy/Di Giulio 2005;Salzmann/Bohk 2008). As suggested by Luy and Di Giulio (2005) we excluded the individuals with unknown survival status from the analysis.…”
Section: Application To the Data Of The German Life Expectancy Surveymentioning
confidence: 99%
“…For 1,047 women (25.3 percent) and 903 men (20.8 percent) the survival status by 1998 is unknown. Tests of the quality of the LES mortality data revealed that the refl ected survival of the LES sample between 1984 and 1998 is representative for the western German population, regardless of whether individuals with unknown survival status in 1998 are included or not (Luy/Di Giulio 2005;Salzmann/Bohk 2008). As suggested by Luy and Di Giulio (2005) we excluded the individuals with unknown survival status from the analysis.…”
Section: Application To the Data Of The German Life Expectancy Surveymentioning
confidence: 99%
“…For 998 women (24.1 percent) and 885 men (20.4 percent) the survival status in 1998 is unknown. Tests of the quality of the LES mortality data revealed that the reflected survival of the LES sample between 1984 and 1998 is representative for the mortality of the western German population, regardless of whether individuals with unknown survival status in 1998 are included or not Di Giulio 2005, Salzmann andBohk 2008). As suggested by Luy and Di Giulio (2005) we excluded the individuals with unknown survival status from the analysis.…”
Section: Mortality Risks Of the Mehm Health Domainsmentioning
confidence: 99%